Inflammatory priming with IL-1β promotes the immunomodulatory behavior of adipose derived stem cells - Colombini, Alessandra; Libonati, Francesca; Cangelosi, Davide; Lopa, Silvia; De Luca, Paola; Coviello, Domenico Antonio; Moretti, Matteo; de Girolamo, Laura (Frontiers in Bioengineering and Biotechnology, 2022)
Inflammatory processes contribute to osteoarthritis (OA) severity and progression. Mesenchymal stem cells, particularly those derived from adipose tissue (ASCs), are able to sense and control the inflammatory environment. This immunomodulatory potential can be boosted by different priming strategies based on inflammatory stimulation. The aim of the present study is to investigate the transcriptional modulation of a huge panel of genes and functionally verify the predicted immunomodulatory ability of ASCs after IL-1β priming. ASCs were isolated from adipose tissue obtained from 3 donors and expanded. After stimulation with 1 ng/mL of IL-1β for 48 hours, cells were collected for gene array and functional tests. Pooled cells from 3 donors were used for RNA extraction used for gene array analysis. Gene Ontology (GO) enrichment analysis and Gene Set Enrichment Analysis (GSEA) were performed to assess the involvement of the modulated genes after priming in specific biological processes and pathways. Functional co-culture tests of ASCs with T cells and macrophages were performed to assess the ability of primed ASCs to modulate immune cell phenotype. Among the overall genes analyzed in the gene array, about the 18% were up- or down-regulated in ASCs after IL-1β priming. GO enrichment analysis of up- or down-regulated genes in ASCs after IL-1β priming allowed identifying specific pathways involved in the modulation of inflammation and extracellular matrix remodeling. The main processes enriched according to the GSEA are related to the inflammatory response and cell proliferative processes. Functional tests on immune cells showed that primed and non-primed ASCs induced a decrease in the CD3+ T lymphocytes survival rate and an anti-inflammatory macrophage polarization. In conclusion, IL-1β priming represents a tailored strategy to enhance the ability of ASCs to direct macrophages towards an anti-inflammatory phenotype and, consequently, improve the efficacy of ASCs in counteracting the OA inflammatory component.